Boosting the Potential of Chemotherapy in Advanced Breast Cancer Lung Metastasis via Micro‐Combinatorial Hydrogel Particles. Issue 10 (22nd January 2023) - Palange, Anna Lisa; Mascolo, Daniele Di; Ferreira, Miguel; Gawne, Peter J.; Spanò, Raffaele; Felici, Alessia; Bono, Luca; Moore, Thomas Lee; Salerno, Marco; Armirotti, Andrea; Decuzzi, Paolo
Abstract: Breast cancer cell colonization of the lungs is associated with a dismal prognosis as the distributed nature of the disease and poor permeability of the metastatic foci challenge the therapeutic efficacy of small molecules, antibodies, and nanomedicines. Taking advantage of the unique physiology of the pulmonary circulation, here, micro‐combinatorial hydrogel particles (µCGP) are realized via soft lithographic techniques to enhance the specific delivery of a cocktail of cytotoxic nanoparticles to metastatic foci. By cross‐linking short poly(ethylene glycol) (PEG) chains with erodible linkers within a shape‐defining template, a deformable and biodegradable polymeric skeleton is realized and loaded with a variety of therapeutic and imaging agents, including docetaxel‐nanoparticles. In a model of advanced breast cancer lung metastasis, µCGP amplified the colocalization of docetaxel‐nanoparticles with pulmonary metastatic foci, prolonged the retention of chemotoxic molecules at the diseased site, suppressed lesion growth, and boosted survival beyond 20 weeks post nodule engraftment. The flexible design and modular architecture of µCGP would allow the efficient deployment of complex combination therapies in other vascular districts too, possibly addressing metastatic diseases of different origins. Abstract : Micro‐Combinatorial hydroGel Particles (µCGP) with a natural tropism for the pulmonary circulation are realized via soft lithography to amplify the deposition of cytotoxic agents in cancer metastasis. In advanced triple negative breast cancer lung metastasis models, µCGP carrying docetaxel nanomedicines boosted the potential of chemotherapy extending survival beyond 5 months.